Overview of Brinjal (Solanum melongena L.) Pests and Their Management: A Review - Dwarka, Nisha Chadar, Shobharam Thakur, Sheeren Parveen, Shradha Parmar; Maneesha, Manoj Kumar Ahirwar (Archives of Current Research International, 2024)
Brinjal (eggplant or aubergine), a widely cultivated vegetable in tropical and subtropical regions, faces significant threats from a variety of insect pests. These pests cause substantial damage at different stages of crop growth, leading to reduced yields and compromised fruit quality. This review provides a comprehensive overview on the major insect pests that affect brinjal cultivation, focusing on their biology, damage mechanisms, and current management practices. Special emphasis is placed on integrated pest management (IPM) strategies, combining cultural, biological and chemical control methods to promote sustainable brinjal production.